Are haplotypes in a single methotrexate pathway more predictive for response in rheumatoid arthritis than in different pathways?. (April 2018) - Soukup, Tomas; Barvik, Ivan; Nekvindova, Jana; Veleta, Tomas; Kubena, Ales A; Duintjer Tebbens, Jurjen; Pavek, Petr; Dosedel, Martin
Letter to the editor with respect to: Lima A, Bernardes M, Azevedo R, Seabra V and Medeiros R. Moving toward personalized medicine in rheumatoid arthritis: SNPs in methotrexate intracellular pathways are associated with methotrexate therapeutic outcome. Pharmacogenomics 17(15), 1649–1674 (2016).